Exploring the early diagnostic value of MRI for type I stress fractures: a retrospective analysis based on imaging manifestations - Lu, Hui; Wang, Cailin; Wang, Leilei; Gao, Xuefeng; Li, Ruquan; Jin, Xiaofeng; Tang, Jun; Guan, Sen (Frontiers in Surgery, 2025)
ObjectiveTo compare the positive rate of early diagnosis and the detection rate of fracture signs in Type I stress fractures using x-ray, CT, and MRI.MethodsA total of 56 patients with Type I stress fractures admitted to the 904st Hospital of the PLA Joint Logistics Support Force from January 2011 to June 2021 were included in the retrospective analysis, including 35 cases of tibial stress fractures (tibia group) and 21 cases of femoral stress fractures (femur group). The positive rate of early diagnosis and the detection rates of visible fracture lines, periosteal reaction, callus formation, surrounding soft tissue swelling, and marrow cavity signal changes were compared between x-ray, CT, and MRI.Results(1) The positive rate of early diagnosis of MRI in the tibia and femur groups were significantly higher than those of x-ray and CT examinations, and the differences were statistically significant (P < 0.05). (2) In the tibia group, MRI had significantly higher detection rates than x-ray and CT examinations for visible fracture lines, periosteal reaction, surrounding soft tissue swelling, and marrow cavity signal changes, and the differences were statistically significant (P < 0.05). There was no significant difference in the detection rate of callus formation (P > 0.05). (3) In the femur group, MRI had significantly higher detection rates than x-ray and CT examinations for visible fracture lines, surrounding soft tissue swelling, and marrow cavity signal changes, and the differences were statistically significant (P < 0.05). There was no significant difference in the detection rates of periosteal reaction and callus formation (P > 0.05).ConclusionBased on the definitely diagnostic advantages of MRI for signs such as visible fracture line, surrounding soft tissue swelling, and marrow cavity signal changes, it shows higher accuracy and application value in the early diagnosis of type Ⅰ stress fractures.